Cervical Cancer Screening Among Women Who Gave Birth in the US-Mexico Border Region, 2005: The Brownsville-Matamoros Sister City Project for Women's Health - Brian C. Castrucci, MA; Alonso Echegollen Guzmán, MD; Mona Saraiya, MD, MPH; Brian R. Smith, MD, MPH; Kayan L. Lewis, PhD; Steven S. Coughlin, PhD; Ginger L. Gossman, PhD; Jill A. McDonald, PhD; illary Foulkes, MPH; Gita Mirchandani, PhD; Luz Correa-Nieto Canedo, MD; Imelda M. Garcia, MPH; et al. (Centers for Disease Control and Prevention, 2008)
IntroductionThe objective of this study was to examine correlates of ever having had a Papanicolaou (Pap) test among women who recently delivered a live infant and who resided near the US-Mexico border.MethodsThis cross-sectional study included women who delivered a live infant in Matamoros, Mexico (n = 488) and Cameron County, Texas (n = 453). Women were interviewed in the hospital before discharge between August 21 and November 9, 2005. Multivariable logistic regression was used to estimate the odds of ever having had a Pap test.ResultsSignificantly fewer Matamoros women (62.1%) than Cameron County women (95.7%) reported ever having had a Pap test. Only 12% of Matamoros women said they received their most recent Pap test during prenatal care, compared with nearly 75% of Cameron County women. After adjusting for potential confounders, the odds of ever having had a Pap test were 7.41 times greater in Cameron County than in Matamoros (95% confidence interval, 4.07-13.48).ConclusionThe Healthy Border 2010 goals are to cut cervical cancer mortality by 20% to 30% in the border region. The significant difference in Pap test prevalence among our survey respondents may reflect that routine prenatal Pap testing is more common in the United States than in Mexico. Because women who are receiving prenatal care have increased interaction with health care providers, Matamoros providers may need to be educated about the need to screen for cervical cancer during this time.